2008
DOI: 10.1063/1.2919119
|View full text |Cite
|
Sign up to set email alerts
|

The range of ambient radius for an active bubble in sonoluminescence and sonochemical reactions

Abstract: Numerical simulations of nonequilibrium chemical reactions inside an air bubble in liquid water irradiated by ultrasound have been performed for various ambient bubble radii. The intensity of sonoluminescence (SL) has also been calculated taking into account electron-atom bremsstrahlung, radiative attachment of electrons to neutral molecules, radiative recombination of electrons and ions, chemiluminescence of OH, molecular emission from nitrogen, etc. The lower bound of ambient radius for an active bubble in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 50 publications
9
131
0
Order By: Relevance
“…This is of course dependent on the size of the bubbles involved. This issue is far from being closed, but modern experimental observations [80] and theoretical results [81,82] suggest that the chemically active bubbles are in fact much smaller than the resonant radius, at least at low frequency. Concerning the dissemination of OH · radicals, this strongly depends on whether or not the bubble breaks up in the final stages of the collapse.…”
Section: Influence Of the Ultrasonic Frequencymentioning
confidence: 93%
“…This is of course dependent on the size of the bubbles involved. This issue is far from being closed, but modern experimental observations [80] and theoretical results [81,82] suggest that the chemically active bubbles are in fact much smaller than the resonant radius, at least at low frequency. Concerning the dissemination of OH · radicals, this strongly depends on whether or not the bubble breaks up in the final stages of the collapse.…”
Section: Influence Of the Ultrasonic Frequencymentioning
confidence: 93%
“…In the ultrasonic sound field, all the bubbles are force to oscillate under the ultrasonic waves, 17 and undergo hundreds of oscillations 18,19 until they collapse. For bubbles oscillating under the acoustic waves, the radiated pressure wave p r could be expressed 20 by…”
Section: Resultsmentioning
confidence: 99%
“…This approach works by stabilizing the bubble size distribution within the active radius range, since active bubbles oscillate strongly as a response to the applied acoustic pressure. According to Yasui et al (2008), the active radius range spans from the Blake threshold to radii on the order of linear resonance radii. However, Hauptmann et al (2013) reported the strongest cavitation activity when the bubble size distribution was centered on the linear resonance size.…”
Section: Effects Of Acoustic Pressure Frequency and Durationmentioning
confidence: 99%
“…Therefore, knowledge about the size distribution of cavitation bubbles is critical for promoting or suppressing the aforementioned physical effects in order to optimize or minimize, respectively, the corresponding cavitation activity. Earlier studies have demonstrated that the equilibrium radius of a cavitation bubble encompasses a range of radii rather than a single linear resonance radius calculated using the linear equation for a given frequency (Yasui et al 2008;Yasui 2002). Furthermore, because of nonlinearity, the actual equilibrium radii of cavitation bubbles are always smaller than the calculated single value (Yasui 2002;Luther et al 2001;Lee et al 2005).…”
mentioning
confidence: 97%